2007
DOI: 10.1093/nar/gkm1035
|View full text |Cite
|
Sign up to set email alerts
|

Activation of DNA strand exchange by cationic comb-type copolymers: effect of cationic moieties of the copolymers

Abstract: We have previously reported that poly(l-lysine)-graft-dextran cationic comb-type copolymers accelerate strand exchange reaction between duplex DNA and its complementary single strand by >4 orders of magnitude, while stabilizing duplex. However, the stabilization of the duplex is considered principally unfavourable for the accelerating activity since the strand exchange reaction requires, at least, partial melting of the initial duplex. Here we report the effects of different cationic moieties of cationic comb-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 40 publications
(55 reference statements)
2
24
0
Order By: Relevance
“…In future studies, it will also be interesting to test thermostable RNA ligases (Blondal et al 2003(Blondal et al , 2005 as well as the influence of additives such as PEG-8000 (Miyoshi and Sugimoto 2008) or compounds such as cationic comb-type copolymers (CCC), both of which enhance the dynamic of RNA folding (Kim et al 2003;Choi et al 2007). It is possible that these conditions lead to an increased rate of interconversion between secondary structure and thereby allow for more product accumulation, given that adapters are always used in excess over input RNAs.…”
Section: Discussionmentioning
confidence: 99%
“…In future studies, it will also be interesting to test thermostable RNA ligases (Blondal et al 2003(Blondal et al , 2005 as well as the influence of additives such as PEG-8000 (Miyoshi and Sugimoto 2008) or compounds such as cationic comb-type copolymers (CCC), both of which enhance the dynamic of RNA folding (Kim et al 2003;Choi et al 2007). It is possible that these conditions lead to an increased rate of interconversion between secondary structure and thereby allow for more product accumulation, given that adapters are always used in excess over input RNAs.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] We previously showed that a cationic comb-type copolymer with guanidino groups accelerates SER relative to the unmodified copolymer. 27 Guanidine modification did not significantly alter cationic properties of the copolymer but did change the hydrogen-bonding capacity. The guanidinium ion is also known to have chaotropic effects that destabilize dsDNA, which should accelerate SER.…”
Section: Introductionmentioning
confidence: 92%
“…Binding of DNA to the copolymer was assessed by fluorescence correlation spectroscopy [18,36,37] using an Olympus MF20 single-molecular fluorescence detection system (Olympus, Tokyo Japan). All samples for the fluorescence …”
Section: Dna Binding To Copolymer As Determined By Fluorescence Corrementioning
confidence: 99%
“…To further understand the effect of the copolymer, binding of copolymer to either ssDNA or tetramolecular quadruplex DNA was analyzed by fluorescence correlation spectroscopy [18,36,37]. Since a diffusion time calculated by the autocorrelation analysis of the fluorescence fluctuation is proportional to cubic root of molecular mass, the complex formation of oligonucleotides with the copolymer leads to an increased in the diffusion time.…”
Section: Binding Assay Of the Copolymer To Ssdna And Tetramolecular Qmentioning
confidence: 99%